A novel natural gas hydrate recovery approach by delivering geothermal energy through dumpflooding. (1st April 2020) - Liu, Yongge; Hou, Jian; Chen, Zhangxin; Su, Haiyang; Zhao, Ermeng; Li, Guangming
Highlights: A novel dumpflooding method to recover natural gas hydrates is proposed. A coupled numerical simulation model of the new method is built. The effectiveness of the proposed method is proved. Factors affecting the development performance are analyzed. Abstract: Conventional thermal stimulation methods require a tremendous investment on in surface heating facilities and a sustained investment in continuous heat injection. Using a heat exchange well to deliver geothermal energy via carbon dioxide or water provides a way to greatly reduce the heat injection cost. However, hydrate bearing layers are often found in harsh natural environments (offshore or continental permafrost), where access to and transportation of heat-delivery media are extremely challenging. Therefore, this paper proposes to boost hydrate recovery with geothermal energy delivered through dumpflooding and a coupled numerical model is built to evaluate the performance of the new method. The results indicate that the hydrate dissociation and gas production are greatly enhanced due to the high temperature of the water flowing from the geothermal reservoir to the hydrate bearing layer; therefore, the feasibility of utilizing the dumpflooding method to exploit hydrate bearing layers is proved. Analyses of influential factors suggest that the pore volumes of hydrothermal reservoirs affect both the rate and temperature of water flowing from the hydrothermal reservoir to the hydrate bearing layer. Higher hydrothermal reservoir temperatures and pressures are favorable for hydrate recovery. Nevertheless, energy efficiency drops as the pore volumes, temperature and pressure of hydrothermal reservoirs increase. The pressure loss caused by friction is negligible compared with that caused by gravity and therefore has nearly no influence on performance.